Dampak Perubahan Iklim Terhadap Aktivitas Ekonomi Kota Purwokerto - Lia Munawaroh; Hanifah Nur Amsiah; M. Dwi Andika Djuru; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Climate change has become a serious challenge with far-reaching impacts on various sectors, including economic activities in urban areas such as Purwokerto. This study aims to identify and analyze the effects of climate change on the local economy and the resilience of communities in response to these changes. Employing a descriptive qualitative method through literature review, the study highlights extreme weather phenomena such as heavy rainfall, rising temperatures, and unpredictable climate patterns that significantly disrupt the agricultural sector, traditional markets, infrastructure, and Micro, Small, and Medium Enterprises (MSMEs). The findings reveal that MSMEs suffer losses due to shifts in consumer behavior and supply chain disruptions, while the agricultural sector faces declining productivity caused by irregular planting and harvesting seasons. On the other hand, digitalization and technological adaptation emerge as strategic opportunities to build local economic resilience. Therefore, synergy between digital innovation, adaptive policies, and improved community literacy is essential to strengthen urban economic resilience in the face of climate change threats.